The lost girls of camp forevermore - Fu, Kim (Houghton Mifflin Harcourt, 2018)
"From the award-winning author of For Today I Am a Boy, a gripping and deeply felt novel about a group of young girls at a remote camp--and the night that changes everything and will shape their lives for decades to come A group of young girls descend on Camp Forevermore, a sleepaway camp in the Pacific Northwest, where their days are filled with swimming lessons, friendship bracelets, and camp songs by the fire. Filled with excitement and nervous energy, they set off on an overnight kayaking trip to a nearby island.But before the night is over, they find themselves stranded, with no adults to help them survive or guide them home.The Lost Girls of Camp Forevermore traces these five girls--Nita, Kayla, Isabel, Dina, and Siobhan--through and beyond this fateful trip. We see them through successes and failures, loving relationships and heartbreaks; we see what it means to find, and define, oneself, and the ways in which the same experience is refracted through different people. In diamond-sharp prose, Kim Fu gives us a portrait of friendship and of the families we build for ourselves--and the pasts we can't escape"--